PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1943)
Abstract This article presents problems which were presented by the Board of Examiners of the American Institute of Certified Public Accountants as the first half of the November, 1942, certified public accountants' examination in accounting theory and practice.